2014
DOI: 10.1111/asj.12160
|View full text |Cite
|
Sign up to set email alerts
|

Increased collagen III in culled chicken meat after feeding dietary wood charcoal and vinegar contributes to palatability and tenderness

Abstract: We comprehensively evaluated meat quality in chickens fed a diet consisting of wood charcoal and vinegar (WCV) using food scientific and histological approaches. In culled hens, lipid and fatty acid in Musculus semimembranosus, cooking loss and sensory tests of whole thigh meat, and meat texture of breast meat were observed. In male broilers, cross section of M. semimembranosus was used for observations on muscle area, perimysium, non-collagen total protein and total collagen content, and anti-collagen I and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Several research groups have shown that the quality of chickens’ meat can be significantly improved by feeding of biochar (Cai, Jiang & He, 2011; Kim et al, 2011; Yamauchi, Ruttanavut & Takenoyama, 2010; Yamauchi et al, 2014). It was for example found that no significant weight gain was recorded when fed with 0.5% activated coconut shell biochar but that Serum Glutamine, Oxaloacetic Transminase, Serum Glutamine Phosphate Transminase, Albumin and triglycerides as well as sensory evaluation and weight of abdominal fat, heart and spleen significantly improved while the cholesterol level decreased (Jiya et al, 2013, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Several research groups have shown that the quality of chickens’ meat can be significantly improved by feeding of biochar (Cai, Jiang & He, 2011; Kim et al, 2011; Yamauchi, Ruttanavut & Takenoyama, 2010; Yamauchi et al, 2014). It was for example found that no significant weight gain was recorded when fed with 0.5% activated coconut shell biochar but that Serum Glutamine, Oxaloacetic Transminase, Serum Glutamine Phosphate Transminase, Albumin and triglycerides as well as sensory evaluation and weight of abdominal fat, heart and spleen significantly improved while the cholesterol level decreased (Jiya et al, 2013, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…These substances might become packed in the pores of the corncob, arrive in the intestine without receiving the effects of stomach acid, flow out from the pores into the intestinal lumen, and thus might have an effect on intestinal function, resulting in improved egg performance in the 50ppm DFG + 250ppm FCP and 500ppm FCP groups. The phenomenon of substances packed by charcoal pores was demonstrated using electron microscopic [18].…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon that charcoal pores can become packed with substances was demonstrated using electron microscopy [20].…”
Section: Discussionmentioning
confidence: 99%